Biomedical telemetry: technology and applications - Noor Azmi, Azran Azhim; Yohsuke, Kinouchi; Masatake, Akutagawa (Nova Science Publisher, 2009)
Telemetry is a technology that allows the remote measurement and reporting of information of interest to the system designer or operator. Telemetry typically refers to wireless communications, but can also refer to data transferred over other media, such as a telephone or computer network or via an optical link. This book provides a brief overview of the telemetric technique and how it has evolved over the years as well as its numerous applications.